Consenso de expertos colombianos sobre recomendaciones basadas en evidencia para el diagnóstico, tratamiento y seguimiento del raquitismo hipofosfatémico ligado al cromosoma X (RHLX) (2023)
Background: X-linked hypophosphatemic rickets is a hereditary disease that generates alterations in bone mineral homeostasis. The morbidity of the condition has been variable in previous decades and even contradictory, probably due to the definition of the case and the diagnostic confirmation. Our propose was to generate evidence-informed recommendations for the diagnosis, treatment, and follow-up of patients with suspected or diagnosed XLHR. Results: After the screening and selection process for 1041 documents, 38 were included to answer the questions raised by the developer group. 97 recommendations about the diagnosis, treatment, and follow-up of patients with suspected or diagnosed XLHR were approved by the experts consulted through modified Delphi consensus. The quality of the evidence was low. Conclusions: The recommendations proposed here will allow early and timely diagnosis of X-linked hypophosphatemic rickets, while optimizing resources for its treatment and follow-up and help clarify the burden of disease and improve health outcomes for this population.